PENGARUH PARTISIPASI MASYARAKAT DAN TRANSPARANSI KEBIJAKAN PUBLIK TERHADAP HUBUNGAN ANTARA PENGETAHUAN DEWAN TENTANG ANGGARAN DENGAN PENGAWASAN KEUANGAN DAERAH (Studi di DPRD Provinsi Daerah Istimewa Yogyakarta) - JOHAN ARIFIN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2006)
This study examines the influence of public participation and public policy transparancy on the relationship between budgeting knowledge and budgeting control. The sample was drawn from province of Daerah Istimewa Yogyakarta. There are 47 legislative participated in this study. The hypothesis are tested empirically used multiple regression. The result of the study indicated that, first, budgeting knowledge are statistically significant, positive coeficient indicated that high budgeting knowledge is caused high budgeting control, second, the interaction between public participation with budgeting knowledge are statistically significant, third, the interaction between public policy tranparancy with budgeting knowledge are statistically significant.